Articles of Agreement December 2004. (International Monetary Fund, 2007)
This paper explains purposes and functions of various articles of the IMF. The original members of the IMF are those of the countries represented at the United Nations Monetary and Financial Conference whose governments accept membership before December 31, 1945. The articles describe that the Board of Governors at intervals of not more than five years are expected to conduct a general review, and if it deems it appropriate propose an adjustment, of the quotas of the members. Recognizing that the essential purpose of the international monetary system is to provide a framework that facilitates the exchange of goods, services, and capital among countries, and that sustains sound economic growth, and that a principal objective is the continuing development of the orderly underlying conditions that are necessary for financial and economic stability, each member undertakes to collaborate with the IMF and other members to assure orderly exchange arrangements and to promote a stable system of exchange rates.